The The Role of Project-Based Learning in Fostering Vocational Students' Oral Communication: Teachers' Perspectives - Rindya Sams (ELLITE: Journal of English Language, Literature, and Teaching, 2026)
This qualitative case study explores the contributions of project-based learning (PBL) in a vocational high school English class to students’ oral communication skills. Data on English teachers’ perspectives on PBL were collected through semi-structured interviews with vocational high school English teachers in East Java, Indonesia. Data were analyzed through thematic analysis, which resulted in three emerging themes: creating genuine communication contexts, promoting fluency, accuracy, and confidence, and developing critical 21st-century skills. The findings reveal that project-based learning provides students with sufficient space for genuine oral communication, serves as a catalyst for refining their communication skills, and allocates time for communicating their projects. The findings imply that vocational high school English teachers continue to implement PBL as an innovative teaching method, that policymakers draft regulations for curriculum development aligned with industrial needs, and that they support teacher professional development. Future research could explore the longitudinal impacts of project-based learning on students’ oral proficiency across semesters or grade levels